Distinct Signature of Oxylipid Mediators of Inflammation during Infection and Asymptomatic Colonization by E. coli in the Urinary Bladder - Nandakumar Packiriswamy; Jeff Gandy; Sara N. Smith; Harry L. T. Mobley; Lorraine M. Sordillo; Sargurunathan Subashchandrabose (Hindawi Limited, 2017)
Urinary tract infection (UTI) is an extremely common infectious disease. Uropathogenic Escherichia coli (UPEC) is the predominant etiological agent of UTI. Asymptomatic bacteriuric E. coli (ABEC) strains successfully colonize the urinary tract resulting in asymptomatic bacteriuria (ABU) and do not induce symptoms associated with UTI. Oxylipids are key signaling molecules involved in inflammation. Based on the distinct clinical outcomes of E. coli colonization, we hypothesized that UPEC triggers the production of predominantly proinflammatory oxylipids and ABEC leads to production of primarily anti-inflammatory or proresolving oxylipids in the urinary tract. We performed quantitative detection of 39 oxylipid mediators with proinflammatory, anti-inflammatory, and proresolving properties, during UTI and ABU caused by genetically distinct E. coli strains in the murine urinary bladder. Our results reveal that infection with UPEC causes an increased accumulation of proinflammatory oxylipids as early as 6 h postinoculation, compared to controls. To the contrary, ABEC colonization leads to decreased accumulation of proinflammatory oxylipids at the early time point compared to UPEC infection but does not affect the level of proresolving oxylipids. This report represents the first comprehensive investigation on the oxylipidome during benign ABEC colonization observed in ABU and acute inflammation triggered by UPEC leading to UTI.